Primer relevamiento de hongos aislados de suelos e insectos plagas asociados a cultivos orgánicos de cáñamo industrial (Cannabis sativa L.) en Paraguay - Claudia Elena Gonzalez; David Santiago Gayoso; Alan Salinas; Gustavo A. Bich; María Lorena Castrillo (Universidad Nacional de Asunción, 2023)
The cultivation of Cannabis sativahas gained importance in recent years in Paraguay and other Latin American countries where legal regulations allow its cultivation for medicinal use, as fiber, and also as food. Since several companies apply the organic cultivation model to guarantee quality and certify their product, it is necessary to study biological control alternatives that guarantee sustainable agriculture. In this study, microorganisms present in the soil of Cannabis sativacultivation and those that infected pests found on the plant were isolated and identified. The serial dilution method was used to isolate microorganisms from the soil and direct seeding on specific culture media to isolate them from the bodies of pest insects. The isolated genera from the soil were Rhizopus, Aspergillus, Absidia,Alternaria, Mucor, Penicillium and Fusarium; the isolated genera from pest insects wereCladosporium, Alternaria, Aspergillus, andFusarium. This study is the first report on fungi in soils and pest insects in industrial hemp cultivation in Paraguay.